How do informal agreements and renegotiation shape contractual reference points? - Ernst Fehr; Oliver Hart; Christian Zehnder (Institute for the Study of Labor (IZA), 2011)
Previous experimental work provides encouraging support for some of the central assumptions underlying Hart and Moore (2008)'s theory of contractual reference points. However, existing studies ignore realistic aspects of trading relationships such as informal agreements and ex post renegotiation. We investigate the relevance of these features experimentally. Our evidence indicates that the central behavioral mechanism underlying the concept of contractual reference points is robust to the presence of informal agreements and ex post renegotiation. However, our data also reveal new behavioral features that suggest refinements of the theory. In particular, we find that the availability of informal agreements and ex post renegotiation changes how trading parties evaluate ex post outcomes. Interestingly, the availability of these additional options affects ex post evaluations even in situations in which the parties do not use them.
urn:nbn:de:101:1-201111213234
Keywords: C91; D03; D86; J41; 330; contracts; reference points; fairness; renegotiation; informal agreement; Verhandlungen; Vertragstheorie; Theorie